2010
DOI: 10.1111/j.1365-2214.2010.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational injuries in children and adolescents in emergency services of Aracaju, Brazil

Abstract: Working children and adolescents have been injured during their occupational activities and work-related injuries represent 4% of injuries of external causes in the emergency departments of Aracaju with 5% lethality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…One paper from Finland discussed the impact of agricultural and nonagricultural labor on adolescents as young workers with income with respect to excessive alcohol consumption [ 11 ]. Of the 16 other papers related to agricultural work in general, six papers also related to nonagricultural, nonmining work in various manufacturing and export sales industries like carpet weaving and shoes [ 12 17 ]; four papers also related to nonagricultural, nonmining work, and domestic work like child care, cooking, and cleaning [ 18 – 21 ]; and one paper also related to both nonagricultural work and mining activities [ 22 ]. As previously noted, Amon et al also cited data from a case study in Mali on artisanal small-scale gold mining [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…One paper from Finland discussed the impact of agricultural and nonagricultural labor on adolescents as young workers with income with respect to excessive alcohol consumption [ 11 ]. Of the 16 other papers related to agricultural work in general, six papers also related to nonagricultural, nonmining work in various manufacturing and export sales industries like carpet weaving and shoes [ 12 17 ]; four papers also related to nonagricultural, nonmining work, and domestic work like child care, cooking, and cleaning [ 18 – 21 ]; and one paper also related to both nonagricultural work and mining activities [ 22 ]. As previously noted, Amon et al also cited data from a case study in Mali on artisanal small-scale gold mining [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was also reflected in higher proportions of injuries requiring medical attention in males compared to females. The involvement of males and females in different work sectors has been linked to differences in work-related risk of injury [ 34 , 50 ]. Similar to previous findings, our study showed that working in construction is predominantly a male occupation [ 48 ] and poses a high risk for injury among males; on the other hand, females report more injuries in crafts and other related trade work [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children who had been working for a longer duration were at higher odds of reporting an injury at work. Previous research has shown higher proportions of injury in younger children due to lack of safety awareness, experience, and skills [ 14 , 18 , 50 ]. Children attending school were at higher odds of reporting injury than children receiving no schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos sobre acidentes de trabalho com crianças e adolescentes ainda são poucos no Brasil, tendo sido a maioria publicada há mais de 10 anos, e existem pouquíssimos estudos epidemiológicos utilizando o SINAN e o SIM [20][21][22][23][24][25][26][27][28][29][30] . Mesmo na literatura internacional há poucas publicações sobre o tema e, em geral, os estudos sobre crianças e adolescentes trabalhadores são focados em grupos e ocupações específicas e em setores como agricultura [31][32][33][34][35][36][37] .…”
Section: Discussionunclassified